Unveiling Neurosyphilis: A Case Report on Presentation, Diagnosis, and Therapeutic Approach to Neurosyphilis - Dr. V. Padma, Dr. M. Ishaivanan, Dr. Sathya Priya, Dr. Razook, Dr. Chaitanya, Dr. Sharath Nallaperumal (South Eastern European Journal of Public Health, 2025)
Neurosyphilis is a rare but serious complication of inadequately treated or untreated syphilis. It describes the infection of *Treponema pallidum* in the central nervous system (CNS), the bacterium responsible for syphilis. This condition can present at any stage of syphilis, but it most often occurs years after the initial infection, especially if left untreated. Neurosyphilis can mimic a range of psychiatric and neurological disorders, making it a diagnostic challenge. Despite the global decrease in syphilis cases following the advent of penicillin, there has been a resurgence in recent years, including cases of neurosyphilis, particularly among immunocompromised individuals such as those with HIV. This report discusses a case of neurosyphilis in a 48-year-old male with progressive cognitive decline, focusing on diagnostic, therapeutic, and management approaches.